CLASSROOM MANAGEMENT OF READING INSTRUCTION AT SMP NEGERI 16 BANDA ACEH - Sariakin, Sariakin (Jurnal Sosial Humaniora Sigli, 2020)
The aims of this research are (1) to find out how the teachers prepares classroom management of reading instruction at the second year students of SMP Negeri 16 Banda Aceh, (2) to find out how classroom management of reading instruction is applied by teachers of SMP Negeri 16 Banda Aceh, and (3) to find out the effect of classroom management of reading instruction on the students’ ability of SMP Negeri 16 Banda Aceh in mastering reading comprehension. This study belongs to qualitative research because only describes the situation and condition of applying classroom management in reading instruction at the school. The subjects  this study is two English teachers who teach at the school. The instruments that are used to collect data are observation, interview, and documentation. The data gotten is analyzed by narration procedure and discussed. The result of research shows that the teachers prepare classroom management of reading instruction by preparing lesson plan, materials, and conducive environment for instruction process. Furthermore, the teachers usually apply cooperative learning “The Students Team Achievement Divisions (STAD)” technique in applying classroom management in reading instruction.  In addition,  using various methods or techniques aim to make the students not bored. The classroom management of reading instruction that the teachers apply is in effective category  because it has a good impact on the eighth grade  students’ ability in mastering reading comprehension. It is proved the students’ reading ability is in good category (77.31).Key Words: Classroom Management, Reading Instruction